Essentials of Marketing Research, Global Edition - Malhotra, Naresh K. (Pearson International Content, 2015)
For courses in Marketing Research at two- and four-year colleges and universities An engaging, do-it-yourself approach to marketing research Essentials of Marketing Research: A Hands-On Orientation presents a concise overview of marketing research via a do-it-yourself approach that engages students. Building on the foundation of his successful previous titles–Basic Marketing Research: Integration of Social Media and Marketing Research: An Applied Orientation–author Naresh Malhotra covers concepts at an elementary level, deemphasising statistics and formulas. Sensitive to the needs of today’s undergraduates, Malhotra integrates online and social media content, and provides current, contemporary examples that ground course material in the real world. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.